A high corrosion-resistant hard stainless steel and its preparation process
Through laser cladding and ultrasonic impact processes of nickel-based alloys and reinforced phases, a multi-layer structure is formed, which solves the problems of insufficient corrosion resistance and hardness of existing stainless steels, and achieves high corrosion resistance and wear resistance, which is suitable for many types of field.
Patent Information
- Application Number
- CN202411311672.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-20
AI Technical Summary
The corrosion resistance and hardness of existing stainless steel materials cannot meet actual production needs, and laser cladding has room for optimization as a means of modification.
Laser cladding is carried out using nickel-based alloy and reinforced phase (nickel-packed tungsten carbide powder, cerium oxide, yttrium oxide, lanthanum oxide composite) and combined with ultrasonic impact technology to form a multi-layer structure to improve the corrosion resistance and wear resistance of stainless steel.
It significantly improves the corrosion resistance and surface hardness of stainless steel, meets actual production needs, and improves its wide range of applications.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of stainless steel, in particular to a highly corrosion-resistant hard stainless steel and a preparation process thereof. Background Art
[0002] Laser cladding, also known as laser melting or laser cladding, is a laser-based surface modification technology. The principle is to add cladding material to the surface of the substrate and use a high-energy-density laser beam to melt it together with a thin layer on the surface of the substrate to form a metallurgically bonded additive cladding layer on the surface of the base layer, thereby improving the physical and chemical properties of the substrate. Nowadays, laser cladding is one of the more conventional modification methods for improving the performance of stainless steel materials, but the corrosion resistance and hardness of the stainless steel materials currently available on the market still cannot meet the actual production needs. Therefore, its surface modification process needs to be further optimized.
[0003] Based on the above situation, the present invention discloses a highly corrosion-resistant hard stainless steel and a preparation process thereof. Summary of the invention
[0004] The object of the present invention is to provide a highly corrosion-resistant hard stainless steel and a preparation process thereof, so as to solve the problems raised in the above background technology.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: A preparation process of highly corrosion-resistant hard stainless steel, comprising the following steps:
[0006] Step (1): mixing the nickel-based alloy and the reinforcing phase, stirring evenly, mechanically grinding for 30-40 minutes, drying at 80-85° C., adding a water glass solution, stirring evenly, and obtaining a cladding material; the reinforcing phase is a composite of nickel-coated tungsten carbide powder, cerium oxide, yttrium oxide, and lanthanum oxide;
[0007] Take the steel substrate, grind the surface flat, wash it with anhydrous ethanol and deionized water in turn, dry it, and then pre-place the cladding material on the surface of the steel substrate. The preset thickness of the cladding material is 1.5-4 mm. Dry it at 80-90 ° C for 4-6 hours, and then laser clad it to form a pre-treated steel substrate.
[0008] Step (2): ultrasonic impact is performed on the surface of the pretreated steel substrate, followed by cleaning and drying to obtain the hard stainless steel.
[0009] In the more optimized solution, in step (1), the laser cladding process parameters are: laser power is 1000~1200W, scanning speed is 5~6mm / s, overlap rate is 40%, spot diameter is 3mm, shielding gas is argon, and argon flow rate is 10~12L / min.
[0010] In the more optimized solution, in step (2), the process parameters of ultrasonic impact are: S-type path, impact frequency of 20 kHz, current of 0.2 A, impact time of 100-120 s, and impact amplitude of 15-20 μm.
[0011] In a more optimized solution, in step (1), the nickel-based alloy composition is: by mass fraction, 22-24wt% Cr, 12-14wt% Mo, 3-5wt% Si, and the rest is Ni; the amount of the reinforcing phase is 20-50wt% of the nickel-based alloy.
[0012] In a more optimized solution, in step (1), in the reinforcing phase, the mass ratio of nickel-coated tungsten carbide powder is 95-99wt%, and the mass ratio of cerium oxide, yttrium oxide and lanthanum oxide is 2:1:1.
[0013] In the more optimized solution, in step (1), gradient laser cladding is performed, and the specific steps are as follows:
[0014] Pre-place cladding material A on the surface of the steel substrate, the preset thickness of cladding material A is 1.5~2mm, dry at 80~90℃ for 4~6h, and perform laser cladding once; then pre-place cladding material B on the surface of the steel substrate, the preset thickness of cladding material B is 1.5~2mm, dry at 80~90℃ for 4~6h, and perform laser cladding twice to form a pre-treated steel substrate;
[0015] Among them, in the cladding material A, the amount of the reinforcement phase is 20-30wt% of the nickel-based alloy; in the cladding material B, the amount of the reinforcement phase is 40-50wt% of the nickel-based alloy.
[0016] In a more optimized scheme, in step (1), the preparation steps of nickel-coated tungsten carbide powder are as follows: ammonium fluoride, hydrofluoric acid and nitric acid are mixed to obtain an activation solution; the tungsten carbide powder is placed in the activation solution, ultrasonicated at 25-30°C for 30-40 minutes, settled, separated, washed and dried to obtain an activated powder;
[0017] The activated powder is immersed in a nickel plating solution, and chemical nickel plating is performed under the assistance of ultrasound. The nickel plating temperature is 25-30°C, the nickel plating time is 1-2h, the ultrasonic frequency is 40kHz, and the power is 400W. After taking out, it is washed with deionized water and vacuum dried to obtain nickel-coated tungsten carbide powder.
[0018] In the more optimized solution, the concentration of ammonium fluoride in the activation solution is 3~4g / L, the concentration of hydrofluoric acid is 40~45mL / L, and the concentration of nitric acid is 30~35mL / L; the dosage of each component of the nickel plating solution is: nickel sulfate 25~30g / L, sodium citrate 70~80g / L, sodium hypophosphite 25~30g / L, boric acid 25~26g / L; sodium hydroxide is used to adjust the pH value to 10.
[0019] A more optimized solution is a highly corrosion-resistant hard stainless steel prepared according to any of the preparation processes described above.
[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0021] The invention discloses a highly corrosion-resistant hard stainless steel and a preparation process thereof. The scheme uses stainless steel as a substrate, performs laser cladding on the surface thereof, utilizes nickel-based alloys and reinforcing phases in different proportions, and the reinforcing phases are compounded by nickel-coated tungsten carbide powder, cerium oxide, yttrium oxide and lanthanum oxide to improve the corrosion resistance of the stainless steel. Ultrasonic impact is performed after laser cladding, and the surface hardness and wear resistance of the prepared stainless steel are improved, and the practicality is higher.
[0022] In this scheme, the present application discloses two optimization schemes, one of which is: (1) the nickel-based alloy composition is: by mass fraction, 22-24wt% Cr, 12-14wt% Mo, 3-5wt% Si, and the rest is Ni; the amount of the reinforcing phase is 20-50wt% of the nickel-based alloy. The mass proportion of nickel-coated tungsten carbide powder is 95-99wt%, and the mass ratio of cerium oxide, yttrium oxide, and lanthanum oxide is 2:1:1.
[0023] Under the above parameter limitations, the scheme sets a single-layer laser cladding layer on the surface of the stainless steel substrate. At this time, the composition of the nickel-based alloy is limited, and Cr and Si are introduced. Therefore, the laser cladding of the nickel-based alloy with this formula has excellent corrosion resistance of the stainless steel; at the same time, the scheme performs surface nickel plating on the tungsten carbide powder to form nickel-coated tungsten carbide powder, and uses nickel-coated tungsten carbide powder as the main reinforcement phase. It has higher wettability and dispersibility with nickel-based alloys, more uniform tissue distribution, and with rare earth oxides as auxiliary reinforcement, the product has excellent hardness and wear resistance.
[0024] The second scheme is: (2) In cladding material A, the amount of reinforcement phase is 20~30wt% of the nickel-based alloy, and the nickel-based alloy composition is: by mass fraction, 22~24wt%Cr, 12~14wt%Mo, 3~5wt%Si, and the rest is Ni; in cladding material B, the amount of reinforcement phase is 20~30wt% of the nickel-based alloy, and the nickel-based alloy composition is: by mass fraction, 22~24wt%Cr, 12~14wt%Mo, 3~5wt%Si, and the rest is Ni. Under the above parameter limitations, the scheme sets a double-layer laser cladding layer on the surface of the stainless steel substrate. The design of the double-layer structure can further improve the corrosion resistance of the product. In addition, the scheme adjusts the amount of Si and reinforcement phase of the nickel-based alloy in the bottom layer (cladding material A), and the final product has the best performance.
[0025] The invention discloses a highly corrosion-resistant hard stainless steel and a preparation process thereof. The scheme design is reasonable, the formula of the structural components of each layer of the product is appropriately adjusted, the prepared stainless steel has excellent corrosion resistance, and the surface hardness and wear resistance meet actual production requirements, and can be widely used in many fields. DETAILED DESCRIPTION
[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] In this embodiment, the steel substrate is 361L stainless steel. The particle size of tungsten carbide powder is 20-25 μm. The particle sizes of cerium oxide, yttrium oxide and lanthanum oxide powder are all 30-40 μm.
[0028] Embodiment 1: A process for preparing highly corrosion-resistant hard stainless steel, comprising the following steps:
[0029] Step (1): Mix the nickel-based alloy and the reinforcing phase, stir evenly, grind mechanically for 30 minutes, dry at 80°C, add the water glass solution, stir evenly, and obtain the cladding material; the nickel-based alloy composition is: by mass fraction, 24wt%Cr, 12wt%Mo, 5wt%Si, and the rest is Ni; the amount of the reinforcing phase is 40wt% of the nickel-based alloy, and the amount of the water glass solution added is 6 drops / gram; the mass ratio of the water glass solution is water glass: water = 1:3. The reinforcing phase is a composite of nickel-coated tungsten carbide powder, cerium oxide, yttrium oxide and lanthanum oxide, the mass proportion of the nickel-coated tungsten carbide powder is 98wt%, and the mass ratio of the cerium oxide, yttrium oxide and lanthanum oxide is 2:1:1.
[0030] Take the steel substrate, grind the surface flat, wash it with anhydrous ethanol and deionized water in turn, dry it, and then pre-place the cladding material on the surface of the steel substrate. The preset thickness of the cladding material is 1.5mm. Dry it at 80℃ for 6h and perform laser cladding to form a pretreated steel substrate. The laser cladding process parameters are: laser power of 1200W, scanning speed of 5mm / s, overlap rate of 40%, spot diameter of 3mm, protective gas of argon, and argon flow rate of 10L / min.
[0031] Step (2): ultrasonic impact is performed on the surface of the pretreated steel substrate, and then cleaned and dried to obtain the hard stainless steel. The process parameters of the ultrasonic impact are: S-shaped path, impact frequency of 20 kHz, current of 0.2 A, impact time of 120 s, and impact amplitude of 20 μm.
[0032] The preparation steps of nickel-coated tungsten carbide powder are as follows: ammonium fluoride, hydrofluoric acid and nitric acid are mixed to obtain an activation solution; tungsten carbide powder is placed in the activation solution, ultrasonicated at 25°C for 30 minutes, settled, separated, cleaned and dried to obtain an activated powder; the component concentration of ammonium fluoride in the activation solution is 3g / L, the component concentration of hydrofluoric acid is 40mL / L, and the component concentration of nitric acid is 30mL / L.
[0033] The activated powder was immersed in a nickel plating solution, and chemical nickel plating was performed under the assistance of ultrasound. The nickel plating temperature was 25°C, the nickel plating time was 2h, the ultrasonic frequency was 40kHz, and the power was 400W. After being taken out, it was washed with deionized water and vacuum dried to obtain nickel-coated tungsten carbide powder. The dosage of each component of the nickel plating solution was: 25g / L nickel sulfate, 75g / L sodium citrate, 25g / L sodium hypophosphite, and 25g / L boric acid; sodium hydroxide was used to adjust the pH value to 10.
[0034] Embodiment 2: A process for preparing highly corrosion-resistant hard stainless steel, comprising the following steps:
[0035] Step (1): Mix the nickel-based alloy and the reinforcing phase, stir evenly, grind mechanically for 40 minutes, dry at 85°C, add the water glass solution, stir evenly, and obtain the cladding material; the nickel-based alloy composition is: by mass fraction, 24wt%Cr, 12wt%Mo, 5wt%Si, and the rest is Ni; the amount of the reinforcing phase is 50wt% of the nickel-based alloy, and the amount of the water glass solution added is 6 drops / gram; the mass ratio of the water glass solution is water glass: water = 1:3. The reinforcing phase is a composite of nickel-coated tungsten carbide powder, cerium oxide, yttrium oxide and lanthanum oxide, the mass proportion of the nickel-coated tungsten carbide powder is 98wt%, and the mass ratio of the cerium oxide, yttrium oxide and lanthanum oxide is 2:1:1.
[0036] Take the steel substrate, grind the surface flat, wash it with anhydrous ethanol and deionized water in turn, dry it, and then pre-place the cladding material on the surface of the steel substrate. The preset thickness of the cladding material is 2mm. Dry it at 90℃ for 5h and perform laser cladding to form a pretreated steel substrate. The laser cladding process parameters are: laser power of 1200W, scanning speed of 5mm / s, overlap rate of 40%, spot diameter of 3mm, protective gas of argon, and argon flow rate of 10L / min.
[0037] Step (2): ultrasonic impact is performed on the surface of the pretreated steel substrate, and then cleaned and dried to obtain the hard stainless steel. The process parameters of the ultrasonic impact are: S-shaped path, impact frequency of 20 kHz, current of 0.2 A, impact time of 120 s, and impact amplitude of 20 μm.
[0038] The preparation steps of nickel-coated tungsten carbide powder are as follows: ammonium fluoride, hydrofluoric acid and nitric acid are mixed to obtain an activation solution; tungsten carbide powder is placed in the activation solution, ultrasonicated at 25°C for 40 minutes, settled, separated, cleaned and dried to obtain an activated powder; the component concentration of ammonium fluoride in the activation solution is 3g / L, the component concentration of hydrofluoric acid is 40mL / L, and the component concentration of nitric acid is 30mL / L.
[0039] The activated powder was immersed in a nickel plating solution, and chemical nickel plating was performed under the assistance of ultrasound. The nickel plating temperature was 25°C, the nickel plating time was 2h, the ultrasonic frequency was 40kHz, and the power was 400W. After being taken out, it was washed with deionized water and vacuum dried to obtain nickel-coated tungsten carbide powder. The dosage of each component of the nickel plating solution was: 25g / L nickel sulfate, 75g / L sodium citrate, 25g / L sodium hypophosphite, and 25g / L boric acid; sodium hydroxide was used to adjust the pH value to 10.
[0040] Embodiment 3: A process for preparing highly corrosion-resistant hard stainless steel, comprising the following steps:
[0041] Step (1): Mix the nickel-based alloy and the reinforcing phase, stir evenly, grind mechanically for 30 minutes, dry at 80°C, add a water glass solution, stir evenly, and obtain a cladding material; the amount of the water glass solution added is 6 drops / gram; the mass ratio of the water glass solution is water glass: water = 1:3. The reinforcing phase is a composite of nickel-coated tungsten carbide powder, cerium oxide, yttrium oxide and lanthanum oxide; the mass ratio of the nickel-coated tungsten carbide powder is 98wt%, and the mass ratio of the cerium oxide, yttrium oxide and lanthanum oxide is 2:1:1.
[0042] In the cladding material A, the amount of the reinforcing phase is 30wt% of the nickel-based alloy, and the nickel-based alloy composition is: by mass fraction, 24wt% Cr, 12wt% Mo, 3wt% Si, and the rest is Ni.
[0043] In the cladding material B, the amount of the reinforcing phase is 40wt% of the nickel-based alloy, and the nickel-based alloy composition is: by mass fraction, 24wt%Cr, 12wt%Mo, 5wt%Si, and the rest is Ni.
[0044] Take the steel substrate, grind the surface flat, wash it with anhydrous ethanol and deionized water in turn, dry it, and then pre-place the cladding material A on the surface of the steel substrate with a preset thickness of 1.5 mm. Dry it at 90°C for 5 hours, and perform laser cladding once; then pre-place the cladding material B on the surface of the steel substrate with a preset thickness of 1.5 mm. Dry it at 90°C for 5 hours, and perform laser cladding twice to form a pretreated steel substrate.
[0045] The laser cladding process parameters are as follows: laser power is 1200 W, scanning speed is 5 mm / s, overlap rate is 40%, spot diameter is 3 mm, protective gas is argon, and argon flow rate is 10 L / min.
[0046] Step (2): ultrasonic impact is performed on the surface of the pretreated steel substrate, and then cleaned and dried to obtain the hard stainless steel. The process parameters of the ultrasonic impact are: S-shaped path, impact frequency of 20 kHz, current of 0.2 A, impact time of 120 s, and impact amplitude of 20 μm.
[0047] The preparation steps of nickel-coated tungsten carbide powder are as follows: ammonium fluoride, hydrofluoric acid and nitric acid are mixed to obtain an activation solution; tungsten carbide powder is placed in the activation solution, ultrasonicated at 25°C for 30 minutes, settled, separated, cleaned and dried to obtain an activated powder; the component concentration of ammonium fluoride in the activation solution is 3g / L, the component concentration of hydrofluoric acid is 40mL / L, and the component concentration of nitric acid is 30mL / L.
[0048] The activated powder was immersed in a nickel plating solution, and chemical nickel plating was performed under the assistance of ultrasound. The nickel plating temperature was 25°C, the nickel plating time was 2h, the ultrasonic frequency was 40kHz, and the power was 400W. After being taken out, it was washed with deionized water and vacuum dried to obtain nickel-coated tungsten carbide powder. The dosage of each component of the nickel plating solution was: 25g / L nickel sulfate, 75g / L sodium citrate, 25g / L sodium hypophosphite, and 25g / L boric acid; sodium hydroxide was used to adjust the pH value to 10.
[0049] Embodiment 4: A process for preparing highly corrosion-resistant hard stainless steel, comprising the following steps:
[0050] Step (1): Mix the nickel-based alloy and the reinforcing phase, stir evenly, grind mechanically for 40 minutes, dry at 85°C, add a water glass solution, stir evenly, and obtain a cladding material; the amount of the water glass solution added is 6 drops / gram; the mass ratio of the water glass solution is water glass: water = 1:3. The reinforcing phase is a composite of nickel-coated tungsten carbide powder, cerium oxide, yttrium oxide and lanthanum oxide; the mass ratio of the nickel-coated tungsten carbide powder is 98wt%, and the mass ratio of the cerium oxide, yttrium oxide and lanthanum oxide is 2:1:1.
[0051] In the cladding material A, the amount of the reinforcing phase is 30wt% of the nickel-based alloy, and the nickel-based alloy composition is: by mass fraction, 24wt% Cr, 12wt% Mo, 3wt% Si, and the rest is Ni.
[0052] In the cladding material B, the amount of the reinforcing phase is 50wt% of the nickel-based alloy, and the nickel-based alloy composition is: by mass fraction, 24wt%Cr, 12wt%Mo, 5wt%Si, and the rest is Ni.
[0053] Take the steel substrate, grind the surface flat, wash it with anhydrous ethanol and deionized water in turn, dry it, and then pre-place the cladding material A on the surface of the steel substrate with a preset thickness of 1.5 mm. Dry it at 90°C for 4 hours, and perform laser cladding once; then pre-place the cladding material B on the surface of the steel substrate with a preset thickness of 1.5 mm. Dry it at 90°C for 4 hours, and perform laser cladding twice to form a pretreated steel substrate.
[0054] The laser cladding process parameters are as follows: laser power is 1200 W, scanning speed is 5 mm / s, overlap rate is 40%, spot diameter is 3 mm, shielding gas is argon, and argon flow rate is 10 L / min.
[0055] Step (2): ultrasonic impact is performed on the surface of the pretreated steel substrate, and then cleaned and dried to obtain the hard stainless steel. The process parameters of the ultrasonic impact are: S-shaped path, impact frequency of 20 kHz, current of 0.2 A, impact time of 120 s, and impact amplitude of 20 μm.
[0056] The preparation steps of nickel-coated tungsten carbide powder are as follows: ammonium fluoride, hydrofluoric acid and nitric acid are mixed to obtain an activation solution; tungsten carbide powder is placed in the activation solution, ultrasonicated at 25°C for 40 minutes, settled, separated, cleaned and dried to obtain an activated powder; the component concentration of ammonium fluoride in the activation solution is 3g / L, the component concentration of hydrofluoric acid is 40mL / L, and the component concentration of nitric acid is 30mL / L.
[0057] The activated powder was immersed in a nickel plating solution, and chemical nickel plating was performed under the assistance of ultrasound. The nickel plating temperature was 25°C, the nickel plating time was 2h, the ultrasonic frequency was 40kHz, and the power was 400W. After being taken out, it was washed with deionized water and vacuum dried to obtain nickel-coated tungsten carbide powder. The dosage of each component of the nickel plating solution was: 25g / L nickel sulfate, 75g / L sodium citrate, 25g / L sodium hypophosphite, and 25g / L boric acid; sodium hydroxide was used to adjust the pH value to 10.
[0058] Comparative Example 1: Example 4 was used as the control group. In Comparative Example 1, ultrasonic impact was not performed, and the other steps remained unchanged.
[0059] A preparation process of highly corrosion-resistant hard stainless steel comprises the following steps:
[0060] Step (1): Mix the nickel-based alloy and the reinforcing phase, stir evenly, grind mechanically for 40 minutes, dry at 85°C, add a water glass solution, stir evenly, and obtain a cladding material; the amount of the water glass solution added is 6 drops / gram; the mass ratio of the water glass solution is water glass: water = 1:3. The reinforcing phase is a composite of nickel-coated tungsten carbide powder, cerium oxide, yttrium oxide and lanthanum oxide; the mass ratio of the nickel-coated tungsten carbide powder is 98wt%, and the mass ratio of the cerium oxide, yttrium oxide and lanthanum oxide is 2:1:1.
[0061] In the cladding material A, the amount of the reinforcing phase is 30wt% of the nickel-based alloy, and the nickel-based alloy composition is: by mass fraction, 24wt% Cr, 12wt% Mo, 3wt% Si, and the rest is Ni.
[0062] In the cladding material B, the amount of the reinforcing phase is 50wt% of the nickel-based alloy, and the nickel-based alloy composition is: by mass fraction, 24wt%Cr, 12wt%Mo, 5wt%Si, and the rest is Ni.
[0063] A steel substrate was taken, the surface was polished and smoothed, and it was washed with anhydrous ethanol and deionized water in turn, and dried. Then, the cladding material A was pre-placed on the surface of the steel substrate, the preset thickness of the cladding material A was 1.5 mm, and it was dried at 90°C for 4 hours, and laser cladding was performed once; then, the cladding material B was pre-placed on the surface of the steel substrate, the preset thickness of the cladding material B was 1.5 mm, and it was dried at 90°C for 4 hours, and laser cladding was performed twice to obtain the hard stainless steel.
[0064] The laser cladding process parameters are as follows: laser power is 1200 W, scanning speed is 5 mm / s, overlap rate is 40%, spot diameter is 3 mm, protective gas is argon, and argon flow rate is 10 L / min.
[0065] The preparation steps of nickel-coated tungsten carbide powder are as follows: ammonium fluoride, hydrofluoric acid and nitric acid are mixed to obtain an activation solution; tungsten carbide powder is placed in the activation solution, ultrasonicated at 25°C for 40 minutes, settled, separated, cleaned and dried to obtain an activated powder; the component concentration of ammonium fluoride in the activation solution is 3g / L, the component concentration of hydrofluoric acid is 40mL / L, and the component concentration of nitric acid is 30mL / L.
[0066] The activated powder was immersed in a nickel plating solution, and chemical nickel plating was performed under the assistance of ultrasound. The nickel plating temperature was 25°C, the nickel plating time was 2h, the ultrasonic frequency was 40kHz, and the power was 400W. After being taken out, it was washed with deionized water and vacuum dried to obtain nickel-coated tungsten carbide powder. The dosage of each component of the nickel plating solution was: 25g / L nickel sulfate, 75g / L sodium citrate, 25g / L sodium hypophosphite, and 25g / L boric acid; sodium hydroxide was used to adjust the pH value to 10.
[0067] Detection experiment:
[0068] Take the stainless steel samples prepared in Examples 1 to 4 and Comparative Example 1, polish them with fine sandpaper, and test the following properties:
[0069] 1. Hardness: Test the surface microhardness of stainless steel samples with a loading load of 500g and a holding time of 10s. Select 3 to 5 test points during the test and take the average value.
[0070] 2. Corrosion resistance: The corrosive medium is 3.5wt% sodium chloride solution, the test temperature is 25℃, the auxiliary electrode is a platinum electrode, the reference electrode is a saturated calomel electrode, the sample is the working electrode, and the corrosion current density is tested and calculated.
[0071] 3. Wear resistance: A ball mill friction and wear test was conducted with a load of 600g, a rotation speed of 500r / min, a rotation radius of 3mm, a grinding ball diameter of 2mm, a material of GCr15 steel, and a friction time of 30min to test the wear weight loss.
[0072] The specific data are shown in Table 1. In addition, “ / ” in the table means not recorded or not tested.
[0073] Table 1
[0074]
[0075] Conclusion: The present invention discloses a highly corrosion-resistant hard stainless steel and its preparation process. The scheme design is reasonable, the formula of the structural components of each layer of the product is appropriately adjusted, the prepared stainless steel has excellent corrosion resistance, and the surface hardness and wear resistance meet the actual production needs, and can be widely used in many fields.
[0076] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A process for preparing highly corrosion-resistant hard stainless steel, characterized in that: The following steps are involved: Step (1): mixing the nickel-based alloy and the reinforcing phase, stirring evenly, mechanically grinding for 30-40 minutes, drying at 80-85° C., adding a water glass solution, stirring evenly, and obtaining a cladding material; the reinforcing phase is a composite of nickel-coated tungsten carbide powder, cerium oxide, yttrium oxide, and lanthanum oxide; Take the steel substrate, grind the surface flat, wash it with anhydrous ethanol and deionized water in turn, dry it, and then pre-place the cladding material on the surface of the steel substrate. The preset thickness of the cladding material is 1.5-4 mm. Dry it at 80-90 ° C for 4-6 hours, and then laser clad it to form a pre-treated steel substrate. Step (2): performing ultrasonic impact on the surface of the pretreated steel substrate, cleaning and drying to obtain the hard stainless steel; In step (1), gradient laser cladding is performed, and the specific steps are as follows: Pre-place cladding material A on the surface of the steel substrate, the preset thickness of cladding material A is 1.5~2mm, dry at 80~90℃ for 4~6h, and perform laser cladding once; then pre-place cladding material B on the surface of the steel substrate, the preset thickness of cladding material B is 1.5~2mm, dry at 80~90℃ for 4~6h, and perform laser cladding twice to form a pre-treated steel substrate; Among them, in cladding material A, the amount of reinforcement phase is 20~30wt% of the nickel-based alloy; in cladding material B, the amount of reinforcement phase is 40~50wt% of the nickel-based alloy; In the reinforcing phase, the mass ratio of nickel-coated tungsten carbide powder is 95-99wt%, and the mass ratio of cerium oxide, yttrium oxide and lanthanum oxide is 2:1:
1.
2. The process for preparing highly corrosion-resistant hard stainless steel according to claim 1, characterized in that: In step (1), the laser cladding process parameters are: laser power is 1000~1200W, scanning speed is 5~6mm / s, overlap rate is 40%, spot diameter is 3mm, shielding gas is argon, and argon flow rate is 10~12L / min.
3. The process for preparing highly corrosion-resistant hard stainless steel according to claim 1, characterized in that: In step (2), the process parameters of ultrasonic impact are: S-shaped path, impact frequency of 20 kHz, current of 0.2 A, impact time of 100-120 s, and impact amplitude of 15-20 μm.
4. The process for preparing highly corrosion-resistant hard stainless steel according to claim 1, characterized in that: In step (1), the nickel-based alloy composition is: by mass fraction, 22-24wt% Cr, 12-14wt% Mo, 3-5wt% Si, and the remainder is Ni; the amount of the reinforcing phase is 20-50wt% of the nickel-based alloy.
5. The process for preparing highly corrosion-resistant hard stainless steel according to claim 1, characterized in that: In step (1), the preparation steps of nickel-coated tungsten carbide powder are as follows: ammonium fluoride, hydrofluoric acid and nitric acid are mixed to obtain an activation solution; the tungsten carbide powder is placed in the activation solution, ultrasonicated at 25-30°C for 30-40 minutes, settled, separated, washed and dried to obtain an activated powder; The activated powder is immersed in a nickel plating solution, and chemical nickel plating is performed under the assistance of ultrasonic wave. The nickel plating temperature is 25-30°C, and the nickel plating time is 1-2 hours. After being taken out, it is washed with deionized water and vacuum dried to obtain nickel-coated tungsten carbide powder.
6. The process for preparing highly corrosion-resistant hard stainless steel according to claim 5, characterized in that: The component concentration of ammonium fluoride in the activation solution is 3~4g / L, the component concentration of hydrofluoric acid is 40~45mL / L, and the component concentration of nitric acid is 30~35mL / L; the dosage of each component of the nickel plating solution is: nickel sulfate 25~30g / L, sodium citrate 70~80g / L, sodium hypophosphite 25~30g / L, boric acid 25~26g / L; sodium hydroxide is used to adjust the pH value to 10.
7. A highly corrosion-resistant hard stainless steel prepared according to the preparation process according to any one of claims 1 to 6.
Citation Information
Patent Citations
Preparation method for fiber laser clad nickel-based nickel-coated tungsten carbide cladding coating
CN106757010A